Multimodal MRI-optical system for high-resolution structural and functional imaging - Vincent, Anita (2015)
Near-infrared (NIR) based bioimaging modalities use electromagnetic waves in the near-infrared spectral range to study functional changes in living tissue by detecting changes in absorption, fluorescence, or scatter arising from intrinsic chromophores such as oxy- and deoxyhaemoglobin, cytochromes, metabolites etc. while Magnetic Resonance Imaging provides superior soft tissue contrast which makes it the ideal imaging modality for non-invasive visualization of brain architecture. Integrating the two modalities then creates a dual-mode imaging system that combines in vivomolecular and functional imagingwith high-quality anatomic imaging.